The characteristics, influence factors, and regulatory strategies of growth retardation in ruminants: a review - Li, Tao; Raja, Bakhtawar Riaz; Liao, Jie; Zheng, Longqing; Yin, Fuquan; Gan, Shangquan; Sun, Xuemei; Lyu, Gang; Ma, Jian (Frontiers in Veterinary Science, 2025)
Growth retardation represents a main barrier to affect the productivity and efficiency of ruminants production, which is characterized by low growth rate, a disparity between skeletal and physiological maturation, gastrointestinal dysfunction and reduced reproductive performance. This review provides a concise overview of growth retardation in ruminants, and summarizes the key factors that influence their growth and development, including genetics, nutrition, microbiota and environment. Also, this review emphasizes the central role of nutritional management and gastrointestinal development, as well as the regulatory mechanisms involved in growth processes. In addition, recent advances in these aspects are discussed to form an integrative framework aimed at improving physiological function in ruminants. This review provides a comprehensive perspective for understanding the complex mechanism of growth retardation in ruminants, puts forward a theoretical basis for optimizing the production efficiency of ruminants industry and emphasizes the importance of multidisciplinary collaboration to provide a reference for advancing systematic research on growth and development of ruminants.